2012
DOI: 10.1159/000339007
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Serous Borderline Tumor Detected by Conventional Papanicolaou Smear: A Case Report

Abstract: Background: Although the Papanicolaou (Pap) smear was originally designed to detect premalignant cervical lesions and cancer, it has become apparent that malignant cells from extrauterine primaries may also appear in the smears. Here, we report a case of a serous borderline tumor (SBT) of the ovary that was detected by a conventional Pap smear. Case Report: In a 34-year-old woman, who was operated on for a left borderline ovarian tumor 2 years ago, glandular dysplasia was discovered in a Pap smear screening. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
(15 reference statements)
1
6
0
Order By: Relevance
“…The present case describes rare case of a borderline serous tumor detected by Pap smear. To our knowledge there are only six described cases in literature of SBT detected by Pap smear as the first presentation of the disease (8,14,16,17,18,19) and one case of an ovarian seromucinous borderline tumor recurrence (20). Psammoma bodies were found in five of described SBT cases (8,14,16,18,19), two of them with psammoma bodies only (8,14) and others with abnormal glandular cells like in our case.…”
Section: Discussionsupporting
confidence: 46%
“…The present case describes rare case of a borderline serous tumor detected by Pap smear. To our knowledge there are only six described cases in literature of SBT detected by Pap smear as the first presentation of the disease (8,14,16,17,18,19) and one case of an ovarian seromucinous borderline tumor recurrence (20). Psammoma bodies were found in five of described SBT cases (8,14,16,18,19), two of them with psammoma bodies only (8,14) and others with abnormal glandular cells like in our case.…”
Section: Discussionsupporting
confidence: 46%
“…Nwanodi et al stated in a review that 10% to 40% of ovarian cancer demonstrated malignant cells on cervicovaginal cytology [ 5 ]; nine out of 11 were at grade III or a more advanced stage. Tepeoğlu et al reviewed six cases of ovarian serous borderline tumors presented as atypical glandular cells and psammoma bodies in a Pap smear [ 6 ], and none were diagnosed at a FIGO stage less than IIB. We summarize similar cases from the literature in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
“…The conventional Papanicolaou smear probably deserves to be developed not only for early detection of ovarian serous borderline tumours [108] but also for invasive cancers; 41% (9/22) of ovarian cancers were identified using a panel of mutated genes from liquid Papanicolaou smear specimens [109]. …”
Section: Discussionmentioning
confidence: 99%